Time-domain vector representation of monopole transient electromagnetic radiation using Maple software. - Boryssenko, Anatoliy A. (IEEE Antennas & propagation magazine.)
The analytical time-domain vector representation of the transient electromagnetic radiation of a monopole antenna is computed using the Maple software package. This simulation originates directly from the rigorous formulation of the problem via Maxwell's equations. A ramp-function approximation of the antenna excitation current (of arbitrary waveform) is employed. Using the capabilities of Maple, the problem is easily transformed into a compact Maple code. Maple computing enables analytical time-domain three-dimensional vector expressions for the transient radiation field. The fundamental properties of transient radiation are thus characterized qualitatively and quantitatively, assisting with physical interpretation of the results.